Pengaruh Kemudahan Penggunaan, Kepercayaan Konsumen dan Ulasan Terhadap Minat Beli Ulang Platform Shopee: Studi Kasus pada Gen Z di Jabodetabek - Rindu Islamia; Afif Zaerofi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the influence of ease of use, consumer confidence, and reviews on repurchase interest on the Shopee platform among Generation Z in the Jabodetabek area. Titled